CONSTITUTIONAL PROTECTIONS AND THE PLIGHT OF CLIMATE-INDUCED MIGRANTS IN THE SUNDARBAN DELTA: A LEGAL ANALYSIS - Chakraborty, Chayan; Poddar, Arup Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Article 21 of the Indian Constitution guarantees the protection of life and liberty to all individuals. The term ’life’ encompasses more than mere animal existence; it implies the inhibition against deprivation of limbs and the ability to appreciate life in its fullness. This provision prohibits the deprivation of life or any divine endowment, including growth and enjoyment, provided legal rulings uphold its efficacy. Life, as envisioned by Article 21, transcends mere physical survival; it embodies the outward expression of an imperceptible inner activity. A significant development in Indian constitutional jurisprudence is the recognition and enforcement of positive rights of life, stemming from the intersection of social justice, the rule of law, and principles of dignified human existence. These positive rights are supported by the language of Article 21. However, the climate migrants from the Sundarban delta remain excluded from the protections offered by ’life,’ ’liberty,’ ’social justice,’ and ’positive rights.’ The Sundarban region, with its unique ecosystem, has been severely impacted by catastrophic climate change-induced disasters. The inhabitants suffer from the adverse effects of recurrent natural disasters, yet they receive neither assistance nor compensation for their losses, necessitating their migration to safer areas. This paper examines the various causes of migration from the Sundarban due to climate change and analyzes how the rights of these migrants have been infringed upon.